2017
DOI: 10.1242/jeb.146928
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic measurements of post-dive cardiac responses in southern elephant seals (Mirounga leonina) during surfacing at sea

Abstract: Measuring physiological data in free-ranging marine mammals remains challenging, owing to their far-ranging foraging habitat. Yet, it is important to understand how these divers recover from effort expended underwater, as marine mammals can perform deep and recurrent dives. Among them, southern elephant seals (Mirounga leonina) are one of the most extreme divers, diving continuously at great depth and for long duration while travelling over large distances within the Southern Ocean. To determine how they manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…For both juveniles and adults, surface durations increased with the total swimming effort performed during the previous dive. Recent studies suggest that there is a positive relationship between surface duration relative to total dive duration and swimming effort during the previous dive in adult female elephant seals (Day, Joumaa, Bonnel, & Guinet, 2017;Génin et al, 2015;Jouma'a, 2016). Recent studies suggest that there is a positive relationship between surface duration relative to total dive duration and swimming effort during the previous dive in adult female elephant seals (Day, Joumaa, Bonnel, & Guinet, 2017;Génin et al, 2015;Jouma'a, 2016).…”
Section: Physiological Limitsmentioning
confidence: 99%
See 3 more Smart Citations
“…For both juveniles and adults, surface durations increased with the total swimming effort performed during the previous dive. Recent studies suggest that there is a positive relationship between surface duration relative to total dive duration and swimming effort during the previous dive in adult female elephant seals (Day, Joumaa, Bonnel, & Guinet, 2017;Génin et al, 2015;Jouma'a, 2016). Recent studies suggest that there is a positive relationship between surface duration relative to total dive duration and swimming effort during the previous dive in adult female elephant seals (Day, Joumaa, Bonnel, & Guinet, 2017;Génin et al, 2015;Jouma'a, 2016).…”
Section: Physiological Limitsmentioning
confidence: 99%
“…This was especially true for juveniles, where the slope of the relationship between the absolute swimming effort of a dive and the following surface duration was steeper than that of adults ( Figure 6). Day et al (2017) showed that This suggests that slight increases in swimming effort cause juveniles to increase their time at the surface in order to breathe and recover, even if they need to spend less time at the surface compared to adults.…”
Section: Physiological Limitsmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet, the investigation of the mechanisms connecting animal movement to these key processes is limited by our ability to track animals in sufficiently high spatial and temporal resolution at which they sense and respond to various environmental cues. The recent development of bio-logging technologies has significantly contributed to filling the gap in our knowledge, by relating animal movements to physiology (Butler & Jones 1997, Génin et al 2015, Day et al 2017, physical environment (Heupel & Simpfendorfer 2008, Ortega et al 2009 and exploited resources (Guinet et al 2014, Kuhn et al 2015, Goldbogen et al 2015, Wilmers et al 2015, Adachi et al 2017. In this context, high sampling-frequency tracking systems and loggers deployed on wild animals have made possible the recording of information that would have been impossible to get otherwise, without being restric ted by visibility, observer bias, or geographic scale (Brown et al 2013).…”
Section: Introductionmentioning
confidence: 99%